2011
DOI: 10.1007/s10549-011-1700-2
|View full text |Cite
|
Sign up to set email alerts
|

RAD50 and NBS1 are not likely to be susceptibility genes in Chinese non-BRCA1/2 hereditary breast cancer

Abstract: Deleterious mutations in several genes that are involved in repair of damage to DNA have been associated with an increased risk of breast cancer. Recent studies have shown sequence variants in two such genes, RAD50 and NBS1, which can be predisposed to breast cancer. The aim of this study is to elucidate the contribution of RAD50 and NBS1 germline mutations to the etiology of non-BRCA1/2 hereditary breast cancer in China. We conducted a mutational analysis of RAD50 and NBS1 in genomic DNA from 384 Chinese wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 40 publications
3
12
1
Order By: Relevance
“…Therefore, we could not confirm a pathogenic effect of heterozygous p.I171V in breast cancer even though the variant was predicted to be deleterious by both the PolyPhen-2 and SIFT algorithms. Similar to our result, several other casecontrol studies failed to find a significant relationship between heterozygous p.I171V and risk of breast cancer [15,17,18,20]. In addition to p.I171V, another common NBS1 variant, c.657del5, has been tested for its significance in breast cancer.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Therefore, we could not confirm a pathogenic effect of heterozygous p.I171V in breast cancer even though the variant was predicted to be deleterious by both the PolyPhen-2 and SIFT algorithms. Similar to our result, several other casecontrol studies failed to find a significant relationship between heterozygous p.I171V and risk of breast cancer [15,17,18,20]. In addition to p.I171V, another common NBS1 variant, c.657del5, has been tested for its significance in breast cancer.…”
Section: Discussionsupporting
confidence: 90%
“…Cao et al [20] tested variants p.I171V, p.Q185E, and c.657del5 in the NBS1 gene among Chinese non-BRCA1/2 high-risk breast cancer and found that no patient carried the p.I171V or c.657del5 variant. This result was reconfirmed in subsequent research by the same group [18].…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Studies performed on French Canadian and Chinese populations did not detect any PTVs in either high-risk cases or controls (35,36). Overall, by using the fixed and random effects models, we found an aggregated odds ratio for these four studies of 3.10 (95% CI 1.148-8.42) for the NBS1 PTVs.…”
Section: Nbs1 Genementioning
confidence: 65%